HIV‐induced neuroinflammation inhibits oligodendrocyte maturation via glutamate‐dependent activation of the PERK arm of the integrated stress response. Issue 9 (31st May 2021) - Roth, Lindsay M.; Akay‐Espinoza, Cagla; Grinspan, Judith B.; Jordan‐Sciutto, Kelly L.
Abstract: Despite combined antiretroviral therapy (cART), HIV‐associated neurocognitive disorder (HAND) affects 30–50% of HIV‐positive patients. Importantly, persistent white matter pathologies, specifically corpus callosum thinning and disruption of white matter microstructures observed in patients with HAND despite viral control through cART, raise the possibility that HIV infection in the setting of suboptimal cART may perturb oligodendrocyte (OL) maturation, function and/or survival, influencing HAND persistence in the cART era. To examine the effect of HIV infection on OL maturation, we used supernatants of primary human monocyte‐derived macrophages infected with HIV (HIV/MDMs) to treat primary cultures of rat oligodendrocyte precursor cells (OPCs) during their differentiation to mature OLs. Using immunostaining for lineage‐specific markers, we found that HIV/MDMs significantly inhibited OPC maturation. Based on our previous studies, we examined the potential role of several signaling pathways, including ionotropic glutamate receptors and the integrated stress response (ISR), and found that AMPA receptors (AMPAR)/kainic acid (KA) receptors (KARs) mediated the HIV/MDMs‐induced defect in OL maturation. We also found that the treatment of OPC cultures with glutamate or AMPAR/KAR agonists phenocopied this effect. Blocking ISR activation, specifically the PERK arm of the ISR, protected OPCs from HIV/MDMs‐mediated inhibition of OL maturation. Further, while glutamate, AMPA, and KA activated the ISR, inhibition of AMPAR/KAR activation prevented ISR induction in OPCs and rescued OL maturation. Collectively, these data identify glutamate signaling via ISR activation as a potential therapeutic pathway to ameliorate white matter pathologies in HAND and highlight the need for further investigation of their contribution to cognitive impairment. Main Points: HIV‐infected monocyte derived macrophage supernatants (HIV/MDMs) inhibit oligodendrocyte maturation; this is mediated by AMPA/KARs and the PERK arm of the integrated stress response (ISR). AMPARs partially drive HIV/MDMs‐induced activation of the ISR.